Mast Cell Responses in Female Somatic Antigen Non- Sensitized and Sensitized Albino Rats During Experimental Ascariasis - S.S. Lal2, Monika Yadav1* and (Recent Research in Science and Technology, 2011)
Mast cells remain one of the most enigmatic cells in the body and they play important role in cellular immunity. Ascariasis is a global disease and its play a major role in the etiology of childhood malnutrition. The recent estimates reveal that 1.4 billion individuals are infected and thousands of deaths per year occur due to intestinal obstruction, mass dysentery syndrome or severe iron deficiency anemia. In present study mast cells were studied in female somatic antigen immunized and subsequent challenge infections. Four groups each containing 4 albino rats were used: i) Control ii) Infected iii) Female Somatic antigen immunized and iv) Female somatic antigen immunized and challenge infection. 0.25 ml female somatic antigen with complete adjuvant was injected intra muscularly in thighs of albino rats. The rats sacrificed on 21st day of post challenge infection. Albino rat’s small intestines were examined histological for mast cells. Count of mast cells was made randomly from the muscularis to the mucosal surface in 20 fields. The results were expressed as the number of mast cells per 20 microscopic fields. In present studies the numbers of mast cells were increased during (low and high doses) experimental ascariasis. Biogenic substances released from mast cells would increase the permeability of the mucosa to antibodies and would have an effect on the expulsion of the parasites.